CREATIVE POTENTIAL OF FUTURE SPECIALISTS IN REPAIRING AND MAINTAINING AUTOMOBILES - Hodun , Volodymyr (Professional Pedagogics, 2021)
The relevance of the article lies in the contradiction between the growing need of service centres and repair companies for highly qualified and creative engineering staff and the inconsistent views on the nature, content and structure of creative potential of future specialists in repairing and maintaining automobiles, unfavourable conditions for its development in colleges.The article aims to define, specify the content and justify the structure of creative potential of future specialists in repairing and maintaining automobiles.Research methods include a theoretical analysis of scientific sources - to identify the coverage of the research problem; comparison - to study scientific approaches to solving the research problem; analysis and synthesis - to determine the closest generic and specific characteristics of the phenomenon under study; systematization - to justify its structural components.Results: the concept of “creative potential of future specialists in repairing and maintaining automobiles” has been defined; its content has been clarified’ its structure has been justified; its basic characteristics have been determined.Conclusions: the concept of “creative potential of future specialists in repairing and maintaining automobiles” is an integrative characteristic that contributes to the success of one’s professional activities; this phenomenon is a complex construct with certain components (motivational-axiological, intellectual-creative, cognitive-pragmatist, emotional-volitional and personal-reflexive) and basic characteristics (a synthesis of creative and technical skills; an aptitude for creative technical activities; willingness to discover effective solutions to problems in the field of automobile maintenance, repair, restoration or quality; the ability to systematically combine methodological, theoretical, and polytechnic knowledge; certain personal and professional qualities).
Keywords: creative potential; future specialists in repairing and maintaining automobiles; content and structure of cre-ative potential